THE COMMISSION OF BOOK HISTORY (1966−1990) AS THE LATVIAN BOOK SCIENCE PROMOTER - DREIMANE, JANA (Knygotyra, 2013)
THE COMMISSION OF BOOK HISTORY (1966−1990) AS THE LATVIAN BOOK SCIENCE PROMOTERJANA DREIMANEAbstractIn the article, the role of the Commission of Book History in the establishment and sustainable developmentof the Latvian book science is considered. The minutes of meetings and other materials of the Commission (they have been preserved in the National Library of Latvia) give evidence about the establishmentof the Commission in 1965, its tasks, chairmen and most active participants, its principles and trends of work, initiated academic activities, discussed research works and upcoming publications, as well as about the abolishment of the Commission in 1990. The article gives information on particular decisions of the Commission, which had a significant impact on the further research of Latvian book history.Key words: Latvian book science, history of Latvian book, Latvian book publishing, National Library of Latvia, Academic Library of the University of Latvia